Management procedures of mutual aided housing for low income people - Abiko, Alex Kenya (2008)
This paper presents the results of a research work concerned with management procedures for mutual aided housing, in which three basic management models were investigated: institutional management, co-management and selfmanagement. The study was based on a literature review about housing provision assessment, and used process and product indicators to assess eight housing programs and projects carried out in four different Brazilian states. This study concluded that all initiatives had positive assessments in terms of quality and costs, and pointed out several factors that can define the procedures that should be adopted procedures for different stages of the process, as well as the basic design criteria.